Women's work : how mothers manage flexible working in careers and family life - Young, Zoe (Policy Press scholarship online., 2018)
This book is the first to go inside women's work and family lives in a year of working flexibly. The private labours of going part-time, job sharing, and home working are brought to life with vivid personal stories, concluding that there is an opportunity to make employment and family life work better together.